Lower limb articular scaling and body mass estimation in Pliocene and Pleistocene hominins. Issue 115 (February 2018) - Ruff, Christopher B.; Burgess, M. Loring; Squyres, Nicole; Junno, Juho-Antti; Trinkaus, Erik
Abstract: Previous attempts to estimate body mass in pre-Holocene hominins have relied on prediction equations derived from relatively limited extant samples. Here we derive new equations to predict body mass from femoral head breadth and proximal tibial plateau breadth based on a large and diverse sample of modern humans (avoiding the problems associated with using diaphyseal dimensions and/or cadaveric reference samples). In addition, an adjustment for the relatively small femoral heads of non- Homo taxa is developed based on observed differences in hip to knee joint scaling. Body mass is then estimated for 214 terminal Miocene through Pleistocene hominin specimens. Mean body masses for non- Homo taxa range between 39 and 49 kg (39–45 kg if sex-specific means are averaged), with no consistent temporal trend (6–1.85 Ma). Mean body mass increases in early Homo (2.04–1.77 Ma) to 55–59 kg, and then again dramatically in Homo erectus and later archaic middle Pleistocene Homo, to about 70 kg. The same average body mass is maintained in late Pleistocene archaic Homo and early anatomically modern humans through the early/middle Upper Paleolithic (0.024 Ma), only declining in the late Upper Paleolithic, with regional variation. Sexual dimorphism in body mass is greatest in Australopithecus afarensis (log[male/female] = 1.54), declines in Australopithecus africanus and Paranthropus robustus (log ratio 1.36), and then again in early Homo and middle and late Pleistocene archaic Homo (log ratio 1.20–1.27), although it remains somewhat elevated above that of living and middle/late Pleistocene anatomically modern humans (log ratio about 1.15).